Influence Providing additional income Employees ( TPP ) on Performance Through Employee Job Satisfaction At the Regional Financial and Asset Management Agency (BPKAD) Bima City - Iwan Setiawan; Hermanto Hermanto; Heriani Heriani; Syati Irawati; Reza Fitriansyah (Cita Konsultindo Research Center, 2024)
The amount of Employee Additional Income (TPP) depends on regional financial capacity, whereas previously the amount was determined by the central government. Before the implementation of the TPP honorarium was received based on the amount of time the output was worked on, the TPP was more about equal distribution according to group and class of position. This study aims to examine how Additional Employee Income (TPP) influences performance via job satisfaction among employees of the Bima City Regional Financial and Asset Management Agency (BPKAD). The research employs a quantitative approach with associative research methods. A total of 61 employees from Bima City BPKD participated in the study in 2024. Data was collected using a questionnaire based on a Likert scale. The analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. The findings revealed that Additional Employee Income (TPP) did not significantly impact the performance of Bima City BPKAD employees. TPP is awarded based on output, yet the level of output produced does not influence the amount of TPP received. Consequently, this does not significantly affect employee performance. However, Additional Employee Income (TPP) positively and significantly influences the job satisfaction of Bima City BPKAD employees. Furthermore, job satisfaction has a positive and significant effect on the performance of these employees. As job satisfaction increases, so does employee performance. Additionally, TPP significantly affects performance through job satisfaction among Bima City BPKAD employees, indicating that TPP will be effective if employee job satisfaction rises, subsequently enhancing work discipline, responsibility, and productivity. The government needs to pay attention to assessment indicators as a condition for obtaining additional employee income based on quality and quantity as well as the timeliness of output. The higher the quality and quantity of output produced, the higher the TPP received.